2008
DOI: 10.1359/jbmr.080804
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanism of Decreased Bone in Brtl Mouse Model of OI: Imbalance of Decreased Osteoblast Function and Increased Osteoclasts and Their Precursors

Abstract: ABSTRACT:The Brtl mouse, a knock-in model for moderately severe osteogenesis imperfecta (OI), has a G349C substitution in half of type I collagen ␣1(I) chains. We studied the cellular contribution to Brtl bone properties. Brtl cortical and trabecular bone are reduced before and after puberty, with BV/TV decreased 40-45%. Brtl ObS/BS is comparable to wildtype, and Brtl and wildtype marrow generate equivalent number of colony-forming units (CFUs) at both ages. However, OcS/BS is increased in Brtl at both ages (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
68
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 38 publications
8
68
1
Order By: Relevance
“…Because OIM is marked by the block in osteoblast differentiation, accumulation of immature osteoblast lineage cells may induce changes in bone cellular microenvironment toward enhanced osteoclast differentiation. 19 Our experiments using TNF-␣ antibody showed a partial block of the osteoclastogenesis in the coculture system. Therefore, the higher number and enhanced resorptive activity of osteoclasts formed in coculture with oim/oim osteoblasts can be explained by the synergistic effect of TNF-␣, highly expressed by immature osteoblasts, along with Rankl and M-CSF also produced by osteoblasts.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Because OIM is marked by the block in osteoblast differentiation, accumulation of immature osteoblast lineage cells may induce changes in bone cellular microenvironment toward enhanced osteoclast differentiation. 19 Our experiments using TNF-␣ antibody showed a partial block of the osteoclastogenesis in the coculture system. Therefore, the higher number and enhanced resorptive activity of osteoclasts formed in coculture with oim/oim osteoblasts can be explained by the synergistic effect of TNF-␣, highly expressed by immature osteoblasts, along with Rankl and M-CSF also produced by osteoblasts.…”
Section: Discussionmentioning
confidence: 63%
“…25 Defective collagen present in osteogenesis imperfecta may also trigger the secretion of inflammatory cytokines. 19 This hypothesis is supported by the finding of approximate threefold increase of TNF-␣ expression in oim/oim osteoblasts compared with ϩ/ϩ osteoblasts. In addition, we also found that less mature GFP Ϫ populations in wild-type mice have increased TNF-␣ expression compared with corresponding GFP ϩ populations.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…(56) Conversely, high levels of bone turnover may play a role in clearing the skeleton of deposited bisphosphonate. Pamidronate has been detected in the urine of OI patients 8 years following cessation of treatment, (22) suggesting that despite local bisphosphonate concentration, drug still can be turned over in the body as osteoclasts attempt to remodel treated bone.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were genotyped by polymerase chain reaction (PCR) using genomic DNA from tail biopsies. 36 Tissue examination by fluorescence and confocal microscopy Spleen, thymus, liver, lung, brain, pancreas, kidney, fat, testis, and calvarial bone from killed mice were examined by DMIL-Leica fluorescence microscope (Leica). Mice containing eGFP ϩ cells were used for subsequent studies.…”
Section: Iutmentioning
confidence: 99%